PERBAIKAN PROSEDUR PENGUJIAN PERATURAN PERUNDANG-UNDANGAN DI MAHKAMAH AGUNG - Sholikin, M Nur (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
Regulations under Laws which is the output of political and bureaucratic processes need to be supervised with a review mechanism by judicial power. Supreme Court as a judicial body have an authority to conduct the judicial review. The issue of the effectiveness procedures for judiical review regulation under law in the Supreme Court became the main topic of this research. This research is conducted through normative research methode, descriptive by studied legislation and other relevant library materials. The study concluded that the regulation and implementation for the judicial review application in the Supreme Court do not support the principles of transparency and accountability. Therefore, it is necessary to make revisions to the Supreme Court Regulation No. 1 Year 2011 on the Rights of the Judicial Review. Keywords: Procedures, Testing Laws and Regulations, the Supreme Court